The Crime of Embezzlement in Criminology Studies - Hairunnisa Ismail (Estudiante Law Journal, 2023)
This study aims to identify and analyze the factors causing the crime of embezzlement of money and steps to deal with the crime of embezzlement by the Gorontalo City Police. The type of research used is Emperis research or field research with a case approach. The results of this study indicate that There are 2 factors causing the crime of embezzlement in Gorontalo City, namely internal factors and external factors. Whether it's because of economic, environmental, or educational factors and committing crimes: the efforts made by the Gorontalo City Police in dealing with embezzlement of money, namely by taking preventive steps by conducting patrols, education and legal counseling and repressive (enforcement) provide strict sanctions in accordance with applicable rules